ANALISIS AKUNTABILITAS PERBANDINGAN TARIFINA-CBG’S DAN TARIF RUMAH SAKIT PADA TINDAKAN KATETERISASI JANTUNG DENGAN PEMASANGAN STENT (PERCUTANEOUS CORONARY INTERVENSI)DI RSI AISYIYAH MALANG - Farida Munawaroh; Dwi Nita Aryani; Widanarni Pudjiastuti (JOEL: Journal of Educational and Language Research, 2022)
Aisyiyah Islamic Hospital (RSIA) in Malang is a private hospital with C type that provides cardiac catheterization services with the installation of a Stent or Percutaneous Coronary Intervention (PCI). The payment system in the implementation of the National Health Insurance has been regulated that the payment pattern to advanced level health facilities used INACBGs. This study aims to analyze the accountability of the comparison of INA-CBG's rates and hospital rates for cardiac catheterization with stent placement. This research employs a qualitative approach and descriptive analysis. The study concluded that thecost rates in handling of cardiac catheterization between INA CBGs and RSIA is different. Monitoring, implementing strict business plans and budgets, testing with Ratio Analysis and communicating in the Doctors in Charge of Cardiology Specialist forums are the keys to accountability.